2000
DOI: 10.1109/77.828301
|View full text |Cite
|
Sign up to set email alerts
|

Development of 46-kA Nb/sub 3/Sn conductor joint for ITER Model Coils

Abstract: Ahtrud -The conductor Joint is one of the key technologics for superconducting coils. A butt type joint has been successfully developed for Ihe ITER magnets.The 46kA NbSSn conductors arc conncctcd by the diffuslon bonding technique in vacuum, after the reaction of NbJSn. The advantage o f this joint is low losses against pulse fietd, because the compacted part is very small compared with other types of joint. I5 butt joints have alrcady bcon fabricated in the ITER CS Model Coil, According to the test results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The CS butt joint is the extension from the butt joint developed by JAERI for the CS Model Coil Outer Module [3]. However, there are several differences in fabrication: a) the butt joining tool needs to be assembled and sealed around connecting conductors, and b) the straight section where the joint is made is very short in order to prevent the joint to "bulge" from the winding pack too much.…”
Section: Butt Joint Developmentmentioning
confidence: 99%
“…The CS butt joint is the extension from the butt joint developed by JAERI for the CS Model Coil Outer Module [3]. However, there are several differences in fabrication: a) the butt joining tool needs to be assembled and sealed around connecting conductors, and b) the straight section where the joint is made is very short in order to prevent the joint to "bulge" from the winding pack too much.…”
Section: Butt Joint Developmentmentioning
confidence: 99%
“…In the interface of the joint the strands are highly compacted to a very low void fraction -(5-8%) to ensure large area of the contact. Studies performed by the Japanese Home Team [3] revealed that the diffusion bond takes place only between copper portions of the cross section in the superconducting strands, sleeve and copper strands. The bronze area does not fuse.…”
Section: Butt Joint Designmentioning
confidence: 99%
“…Study [7] performed with ANSYS predicted that the strain of the butt joint interface will be stretched by only slightly less than the jacket -to 0.1%, and the butt joint interface will see 22 kN tensile load. At ultimate strength of the butt joint of 40-50 kN [3] there is a serious concern regarding mechanical and electrical integrity of the joint under such high cyclic load.…”
Section: Structural Analysis Of the Butt Jointmentioning
confidence: 99%
See 2 more Smart Citations